HETEROTIC EXPRESSION FOR DRY POD YIELD AND ITS COMPONENTS IN CHILLI (Capsicum annuumvar. annuum) - N. Rohini; V. Lakshmanan (Journal of Animal and Plant Sciences, 2017)
Heterosis for dry pod yield and related characters in chilli was studied in full diallel crosses involving six genetically diverse inbreds. The hybrids and their potential parental lines differed significantly for all the characters, as evident from their highly significant mean square values. Considering the dry pod yield per se performance, the F1 hybrids LCA 625 K 1 (165.58 g), K 1 Arka Lohit (157.25 g), Pusa Jwala PKM 1 (156.54 g), PKM 1 LCA 625 (155.73), Pusa Jwala K 1(147.40 g) and Arka Lohit LCA 334 (143.10 g) were identified as best hybrids for further exploitation in breeding programme. These six F1 hybrids could be exploited for table purpose due to higher weight and number of fruits along with high yield. Furthermore, these six hybrids exhibited higher magnitude of heterobeltiosis (104.42, 113.95, 140.83, 91.99, 126.77 and 93.38%) and standard heterosis over CO CH1 (18.12, 12.17, 11.67, 11.09, 5.15 and 2.08%) for dry pod yield per plant. Based on per se performance and heterosis, the F1 hybrids LCA 625 K 1 and K 1 Arka Lohit were consistent which could be used for commercial exploitation after its critical evaluation.
Keywords: Chilli; standard heterosis; heterobeltiosis; yield